Factors Associated with The Length of Sick Leave Due to Covid-19 - Betharia Sonata Butarbutar; Nuri Purwito Adi; Levina Chandra Khoe; Marsen Isbayu Putra; Aria Kekalih (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Despite the COVID-19 pandemic, the workers in food manufacturing continue to work. The Government of Indonesia issued a regulation of 10-day isolation for those asymptomatic patients. This regulation implies long sick leave for workers with asymptomatic COVID-19 infection, leading to possible disruption in fulfilling target production. This study aims to understand the factors associated with the length of sick leave due to COVID-19 among food manufacturing workers. Methods: The design of this study was cross-sectional, used 205 workers’ data of confirmed COVID-19 infection, and returned to work from March 2020 – to August 2021. The data were obtained by the company medical team from medical resumes at the companies’ clinics and then sent to Ikatan Dokter Kesehatan Kerja Indonesia (IDKI) Banten. The data was screened as inclusion and exclusion criteria and then analyzed by descriptive test. unpaired T-test and linear regression. Results: The mean length of sick leave of 205 data was 19.3 (± 4,8) days. Treatment facilities, work shifts, and smoking were associated with the length of sick leave (p<0.05). Home Self-isolating, shift, and non-smoking workers had longer sick leave than workers treated at COVID center, non-shift, and smoking workers Conclusion: The mean length of sick leave among food workers in Cilegon is 19.3 (±4,8) days. There is a significant relationship between the length of sick leave with treatment facilities, shift work, and smoking. Treatment facilities were the most dominant factor.